The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages I THE FEEDING OF CHILDREN FROM ONE TO FIVE YEARS This memorandum deals with the feeding of children from one to five years of age, the period of transition from infant to child when physical and intellectual development is rapid, habits are formed and children are particularly susceptible to infectious and other diseases. For growth the diet should be rich in constructive nutrients, while for physical activity it should be rich in energy-giving foods ; the liability to disease necessitates a diet rich in protective nutrients. Care should be taken to guard against the formation of food aversions or prejudices which children generally acquire by copying their elders. Experience has shown that practically all food aversions, except idiosyncrasies, can be abolished by example and by tactful and persistent persuasion. Genuine idiosyncrasies with clinical symptoms, of which perhaps the commonest are those against shellfish and strawberries do, however, exist. This is a different matter from a mere aversion to particular foods which has no physiological basis. Those in charge of the feeding of children should distinguish between the two and should be specially careful not to allow their own likes and dislikes to influence the habits of the children under their care. Everyone concerned with the education of young children has realised the very great importance of using meals as an opportunity for training in self-reliance, good manners and correct behaviour. Every meal should be a social occasion at which the children should learn to behave properly and to be considerate and unselfish. Nutritional Requirements. Children from 1-3 years need about 840-1,000 calories daily and children up to 5 years about 1,300 calories. Protein requirements are about 35-45 grams for children aged 1-3 years, and 45-55 grams for children from 3-5 years. The calcium needed for children up to 5 years is about 1 gram a day and iron 5-8 mg. according to age. Vitamin requirements would be met by intakes of about 3,000 international units of vitamin A, 200-250 of vitamin B.I, 600 I.U. of vitamin C. and 300-500 I.U. of vitamin D. The tables below show how the requirements of children up to 5 years may be met from rationed and certain unrationed foods. They are not suggested as constituting a specimen diet, as there are many other foods available which it would be desirable to include to increase variety and flavour. For instance, the list does not contain any fruit, or such things as barley, rice and other cereals and cereal products. It might also be found possible to obtain two or more eggs weekly, thus enriching the diet in constructive and protective nutrients. Children sometimes dislike vegetables, usually because they are badly cooked. In view of their great nutritional value special pains should be taken to make sure that vegetables are cooked and served in easily digested and attractive forms. The menus in Appendix I, if prepared according to the instructions given, will supply a sufficiency of the essential nutrients. 16255 A 2 127/NU/5/5/1/28